1998
DOI: 10.1002/(sici)1521-3951(199805)207:1<111::aid-pssb111>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

A Semiclassical Approach to the Electron Gas in Two-Dimensional Semiconductor Structures

Abstract: A theory is developed of the density of states (DOS) of the two-dimensional electron gas (2D EG) in semiconductor heterostructures, taking into account the effect of disorder caused by some random field existing in the sample. For a smooth random field, the calculation is carried out within its Gaussian statistics and a semiclassical approach. A simple closed expression thus obtained includes the classical DOS and its quantum correction as well, which describe the DOS of the 2D EG in explicit dependence on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Finally, the high-energy resolution and luminosity of the electron analyzer allowed us to study the shape of the feature. From comparison with recent calculations 15,16 we derived evidence of the broadening of the 2DEG density of states due to the random fields set up by the ionized AM atoms at the surface, already known to produce a strong inhomogeneity of the surface band bending. 17…”
Section: Introductionmentioning
confidence: 96%
“…Finally, the high-energy resolution and luminosity of the electron analyzer allowed us to study the shape of the feature. From comparison with recent calculations 15,16 we derived evidence of the broadening of the 2DEG density of states due to the random fields set up by the ionized AM atoms at the surface, already known to produce a strong inhomogeneity of the surface band bending. 17…”
Section: Introductionmentioning
confidence: 96%
“…It was shown that [21] for taking into account the ionic correlation, we have to incorporate an appropriate correlation factor (less than unity) into the autocorrelation function as follows [12] |U…”
Section: Iii1 Inonized Dopantsmentioning
confidence: 72%
“…As a result, their distribution in space tends to be more homogeneous, so their average field is weakened. 25,26) The ACF of the correlated impurities is proven [27][28][29] to be reduced by some factor,…”
Section: Basic Equationsmentioning
confidence: 99%
“…For instance, following eqs. (14) and (29), the rate of SR scattering exhibits a quadratic dependence on the interface value of the wave function. Then, in accordance with the modification of the wave function in 2S-and 1S-doped samples, mentioned above (Fig.…”
Section: Mobility Enhancementmentioning
confidence: 99%